Comparative Efficacy of Polyherbal Gel and 2% Lignocaine Gel in Managing Parikartika (Acute Fissure-in-Ano): A Pilot Study - Agarwal, Manju; Pathak, Avnish; Agarwal, Riju (Journal of Neonatal Surgery, 2025)
Parikartika, known as fissure-in-ano in modern medicine, is a painful anorectal condition characterized by a longitudinal tear in the anal canal. This study aimed to evaluate the comparative efficacy of a polyherbal gel and 2% lignocaine gel in managing acute fissure-in-ano. The polyherbal gel contained Panchavalkala, Nimba, and Kumari, while the lignocaine gel served as the control. Twenty patients were randomly divided into two groups, with each group receiving local application of the respective gel twice daily after a sitz bath for four weeks. The study assessed the outcomes based on clinical features and adverse drug reactions. The results showed that the polyherbal gel group showed better improvement in terms of relief in symptoms as compared to the lignocaine gel group. The majority of patients were males (85.19%), married (88.88%), and had a Vata-pitta Prakriti (55.56%). Most patients reported passing hard stools (70.37%) and had a Krura Koshtha (48.15%). No significant adverse drug reactions were reported in either group. The study concluded that the polyherbal gel containing Panchavalkala, Nimba, and Kumari could be a good alternative for relieving symptoms, promoting quick healing, and providing an economical option for managing acute fissure-in-ano. Further research with larger sample sizes is needed to validate these findings and explore the potential of Ayurvedic approaches in the management of this painful condition